Nutrient-based Organic Formulations for Sustainable Crop Nutrition and Soil Health: A Critical Appraisal of Mechanisms, Agronomic Evidence and Unresolved Constraints - R. Raman; D. Aishwarya; S. Seenikkannaiyan; D. Suresh (Journal of Advances in Biology & Biotechnology, 2026)
Nutrient-based organic formulations occupy an expanding but conceptually unsettled position between bulk organic amendments and manufactured mineral fertilisers. The category now includes enriched and fortified composts, vermicomposts, organomineral granules, biochar-based composites, anaerobic digestates, microbial inoculant formulations, and non-microbial biostimulants derived from seaweeds, humic substances and protein hydrolysates. These products are promoted simultaneously as nutrient carriers, soil conditioners and physiological enhancers, yet the evidence supporting each of these functions rests on different experimental traditions, different comparison treatments and different outcome variables. This critical narrative review examines how far the published literature supports the claim that nutrient-based organic formulations can deliver both dependable crop nutrition and durable improvement in soil health. Evidence was assembled from open scholarly databases and indexes and appraised for design adequacy, comparator choice, replication, duration and ecological realism rather than for citation frequency alone. Four findings dominate the synthesis. Nutrient release from organic matrices is governed by substrate quality and by soil moisture and temperature, so nutrient supply is inherently asynchronous with crop demand and cannot be treated as equivalent to mineral fertiliser supply at matched nutrient rates. Soil health responses are real but strongly dependent on cumulative carbon input, and improvements in measured indicators are frequently reported without demonstration of a corresponding gain in soil function. Yield responses are highly context dependent, and the largest reported effects arise where the comparison treatment is unfertilised or nutrient limited rather than fully fertilised. Product quality, formulation stability and efficacy claims remain inadequately standardised, which is a principal cause of the inconsistency observed between controlled and field conditions. Priority research needs include comparator-standardised multi-season field trials, mechanistic linkage between indicator change and soil function, and harmonised quality specifications for formulated organic products.